The importance of patient perspectives in lung transplantation - Ferrari, Pisana; Forsberg, Anna; Grossi, Alessandra (Pulmonary Hypertension and Lung Transplantation, 2025)
The consideration of patient experiences has gained significant attention in recent years as part of the broader shift toward patient-centered care. The aim of this chapter is to explore the personal experiences of individuals before and after lung transplantation, highlighting how these experiences are deeply embedded within a network of family and social connections. This chapter emphasizes the importance of addressing the emotional, physical, social, and spiritual well-being of lung transplant recipients. It underscores the need to preserve these aspects of well-being, even in the face of the suffering, fears, and anxieties that accompany the individual journey through disease and transplantation.
Keywords: And after the perioperative period; Doctor-patient communication; Donor-related concerns; During; Patient perspectives before; Person-centered care in lung transplantation; Psychological adjustment; Shared decision-making